Manifestations of Mercy in the Holy Qur’an )Sending of Messengers and Provision( - An Objective Study (Islamic Sciences Journal, 2026)
The text discusses the concepts of manifestations, mercy, and the Qur’an from both linguistic and terminological perspectives, highlighting their legal and scholarly connotations. It emphasizes that divine mercy is a comprehensive principle manifested in gentleness, benevolence, and the conveyance of goodness to servants. It also clarifies that the Qur’an is the Word of God revealed as guidance and mercy for all humankind. The text further explains that among the greatest manifestations of God’s mercy is the sending of messengers and the revelation of scriptures to guide people and bring them out of ignorance and misguidance. It presents provision as an all-encompassing manifestation of divine mercy, whereby God has guaranteed the sustenance of all creatures without exception, combining the assurance of provision with the command to take appropriate means, affirming reliance upon God and detachment from dependence on creation.
Keywords: Manifestations, Mercy, Qur’an, Sending of Messengers, Provision.